TeDia - A Telemedicine-Based Treatment Model for Inpatient and Interprofessional Diabetes Care - Röhling M (Dove Medical Press, 2019)
Martin Röhling,1,* Marcus Redaélli,2,* Dusan Simic,2 Kristina Lorrek,2 Christina Samel,3 Paul Schneider,4 Kerstin Kempf,1 Stephanie Stock,2 Stephan Martin1,5 1West-German Center of Diabetes and Health, Düsseldorf Catholic Hospital Group, Düsseldorf, Germany; 2Institute of Health Economics and Clinical Epidemiology, University Hospital of Cologne, Cologne, Germany; 3Institute of Medical Statistics and Computational Biology, Faculty of Medicine, University of Cologne, Cologne, Germany; 4Düsseldorf Catholic Hospital Group, Düsseldorf, Germany; 5Faculty of Medicine, Heinrich Heine University Düsseldorf, Düsseldorf, Germany*These authors contributed equally to this workCorrespondence: Martin RöhlingWest-German Centre of Diabetes and Health, Düsseldorf Catholic Hospital Group, Hohensandweg 37, Düsseldorf 40591, GermanyTel +49 211-56 60 360 76Fax +49 211-56 60 360 72Email martin.roehling@vkkd-kliniken.deIntroduction: The proportion of hospitalized patients with diabetes as a secondary diagnosis increases continuously. Therefore, we have developed a team-based interprofessional and telemedicine-based diabetes management system named TeDia (“Telemedical Diabetology”) and implemented it in an inpatient setting. The aim of the retrospective real-world study was to show the clinical impact of TeDia following its implementation.Material and methods: TeDia is characterized by an interpersonal and telemedicine-based exchange of hospital routine data between specially trained nurses (“diabetes managers”) and external diabetologists. It was implemented in three acute hospitals of the Düsseldorf Catholic Hospital Group in Düsseldorf, Germany. Clinical awareness of diabetes, diabetes-related complications and diagnosis-related group (DRG)-based revenues were analyzed using ICD routine coding. Furthermore, the frequency of HbA1c determinations as well as hospitalization days were investigated.Results: Before (2010), during (2012) and after the implementation of TeDia (2014), the number of patients with ICD coding for diabetes, decompensated diabetes, diabetic neuropathy, diabetic nephropathy as well as complicated diabetes increased by +18%, +93%, +101%, +113% and +89%, respectively. Using the same DRG grouper, revenues increased by +53% (from 27 (2013) to 42 (2014) DRG points). Frequency of HbA1c determinations rose by +85%, whereas the time for an average length of stay decreased by −12% (−0, 91 days) in comparison to patients without diabetes.Conclusion: TeDia improved clinical awareness for diabetes and its complications. This new treatment model increased revenues and reduced hospital days indicating enhanced treatment quality. Our findings emphasize the necessity of novel technologies in inpatient settings for the improvement of efficacy, safety and efficiency of diabetes care.Keywords: telemedicine, diabetes, inpatient care